2016
DOI: 10.1037/pas0000208
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of a brief version of the Penn State Worry Questionnaire in African Americans and European Americans.

Abstract: The reliable and valid assessment of chronic worry in African Americans is vital when attempting to draw cross-cultural comparisons between African Americans and other ethnic groups. As such, the current study examined the psychometric properties of a brief version of a gold standard assessment of chronic worry, specifically the Penn State Worry Questionnaire-Abbreviated (PSWQ-A; Hopko et al., 2003) in a college sample of African Americans (n = 100) and European Americans (n = 121). Results indicated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 50 publications
(117 reference statements)
0
16
1
Order By: Relevance
“…As shown in Table 2, the two-factor model exhibited measurement invariance (or relatively equal fit the two-factor structure of the MEIM) as model parameters were progressively constrained to be equal between the two samples. Importantly, such measurement invariance warrants the use of the two factor structure to compare mean ethnic identity scores between samples [39]. In our final invariant model, the Affirmation/Belonging and Exploration subscales were positively correlated (r = .774, p < .001).…”
Section: Confirmatory Factor Analysismentioning
confidence: 86%
See 2 more Smart Citations
“…As shown in Table 2, the two-factor model exhibited measurement invariance (or relatively equal fit the two-factor structure of the MEIM) as model parameters were progressively constrained to be equal between the two samples. Importantly, such measurement invariance warrants the use of the two factor structure to compare mean ethnic identity scores between samples [39]. In our final invariant model, the Affirmation/Belonging and Exploration subscales were positively correlated (r = .774, p < .001).…”
Section: Confirmatory Factor Analysismentioning
confidence: 86%
“…After establishing a good fitting model within our full sample, we conducted a multigroup confirmatory factor analysis according to guidelines outlined by Byrne [37] and Kline [38] to compare the overall fit of the MEIM factor structure between our sample of Southern (n=150) and non-Southern (n=145) African Americans. Such analyses "systemically compares the unstandardized solutions of measurement models with differing constrained parameters (e.g., factor loadings) to identify any non-equivalence between groups" [39]. Specifically, the authors first constrained factor loadings to be equal between the two samples and compared the model fit to an unconstrained model (i.e., all parameters allowed to vary freely between the two samples).…”
Section: Statistical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, confirmatory factor analysis (CFA) in the study by Nuevo et al (2007) revealed gender non-invariance such that women endorsed items related to situational or contingency-related worries higher than men. Extending these findings, DeLapp et al (2016) found strong PSWQ-A measurement equivalence between European Americans and African Americans. Also, in that study, European Americans tended to report greater symptom severity on items assessing uncontrollability of chronic worry.…”
Section: Cross-cultural and Gender Invariance Of Five Common Symptom And Cognitive Vulnerabilitymentioning
confidence: 53%
“…The 8-item PSWQ-A measures uncontrollability and excessiveness of worry (Hopko et al, 2003). It has shown moderate-to-large retest reliability (r = .63-.87) and internal consistency (α = .87-.94) in European American and African American samples (DeLapp et al, 2016). Internal consistencies were also strong in the present sample (U.S.: ω = .93; SG: ω = .92; Males: ω = .93; Females: ω = .93).…”
Section: Penn State Worry Questionnaire-abbreviated (Pswq-a)mentioning
confidence: 99%